Implementasi Sistem Pengendalian Intern Pemerintah (SPIP) Dalam Perspektif Islam - A. Arisman; Aries Putriyani; Ahmad Afandi (Akuntabilitas, 2018)
The purpose of this study is to explore the implementation of Government’s Internal Control System in Islamic perspective. This research used descriptive method with Al-Qur’an, Hadith, regulations, books and articles as the sources of this research. Although Internal Control’s Comprehensive Framework and Guidance developed by COSO in 1992, but it had implemented by muslim leader since Nabi Muhammad’s era until Turki Utsmani Dynasty’s era. Five components of Internal Control that formed by COSO and adopted by government in PP No.60 2008 are control environment, risk assessment, control activities, information and communication, and monitoring, each components have subcomponents; and for control environment we suggest to add with the spiritual, nature and style of leadership. The basic component of internal control is control environment, because it has a role as a protector for other components. If control environment has worked properly, then it will minimize a risk, control activities would be implemented simply, information and communication will run smoothly and internal control could be monitored periodically.